Immobilization of Lipase on Silver Nanoparticles via Adhesive Polydopamine for Biodiesel Production - Kanchana Dumri (2018)
© 2014 Kanchana Dumri and Dau Hung Anh. Biodiesel production technology is competitive in terms of low cost and alternative source of energy which should be not only sustainable but also environmentally friendly. Designing of the lipase immobilization for biodiesel production has a remarkable impact and is still challenging. In this work, biodiesel production from soybean oil was enhanced and facilitated by using a novel biocatalyst consisting of commercial lipase (EC 3.1.1.3), silver nanoparticles, and polydopamine. Silver nanoparticles (AgNPs) were synthesized with a size range of 10-20 nm. Polydopamine (PD) was delivered by the self-polymerization of dopamine in 10 mM Tris-HCl pH 8.5 and simultaneously coated the AgNPs to form a PD/AgNPs complex. Lipase was immobilized on the PD/AgNPs complex surface via covalent bonds to form a tailor-made biocatalyst consisting of immobilized lipase/PD/AgNPs complex (LPA). The formation and morphology of each composition were characterized by UV-Vis spectroscopy and scanning electron microscope (SEM). Significantly, gas chromatography analysis showed a remarkable biodiesel production yield of 95% by using the LPA complex at 40°C for 6-hours reaction time, whereas the yield was 86% when using free lyophilized lipase. The LPA complex was apparently reusable after 7 batches and the latter conversion rate of soybean oil was decreased by only 27%.